Spontaneous and postsurgical/traumatic Klebsiella pneumoniae meningitis: two distinct clinico-microbiological entities. (January 2022) - Rollin, Guillaume; Rossi, Benjamin; Brisse, Sylvain; Decré, Dominique; Leflon-Guibout, Véronique; Bert, Frédéric; Hoffmann, Isabelle; Decousser, Jean-Winoc; Fantin, Bruno; Lefort, Agnès
Highlights: Spontaneous K. pneumoniae meningitis is caused by hypervirulent strains Spontaneous K. pneumoniae meningitis is a very serious infection, with high mortality Postsurgical/traumatic K. pneumoniae meningitis has a better prognosis Abstract: Objectives: To analyze and compare the characteristics and outcomes of spontaneous meningitis (SM) versus postsurgical/traumatic meningitis (PSTM) due to Klebsiella pneumoniae . Methods: A retrospective multicentric cohort study of all K. pneumoniae meningitis cases managed between January 2007 and May 2018 was carried out in seven university hospitals in the Paris area. The microbiological characteristics of 16 available K. pneumoniae isolates were further analyzed, and the genomes of seven of those isolated from SM were sequenced. Results: Among 35 cases, 10 were SM and 25 were PSTM. SM cases more severe than PSTM cases, with higher septic shock ( p  = 0.004) and in-hospital mortality rates ( p  = 0.004). In contrast, relapse occurred in five patients from the PSTM group versus no patients from the SM group. All K. pneumoniae strains recovered from SM but none of those recovered from PSTM displayed hypervirulent phenotypic (positive string test) and genotypic (genes corresponding to capsular serotypes K1 or K2; virulence genes rmpA and iutA ) characteristics ( p < 0.0001). PSTM tended to be more frequently polymicrobial ( p  = 0.08) and caused by an extended-spectrum β-lactamase producing strain ( p  = 0.08) than SM. Conclusions: SM and PSTM are two entities differing both from a clinical and a microbiological standpoint. SM appears to be a more serious infection, induced by hypervirulent K. pneumoniae strains.